Efektivitas Pembelajaran Fikih Menggunakan Media YouTube di Kelas XI SMA Ardaniah Serang Banten - Sugianto, Relly; Aspandi, Aspandi; Hidayatullah, Hidayatullah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
YouTube functions as software designed for tools, manipulation, and the communication of information. The aim of this investigation was to assess the impact of implementing YouTube as an effective platform for Islamic Religious Education. This research employs a qualitative design with SMA Ardaniah Serang Banten as the location setting. Data collection methods involve observation, interviews, and documentation. The analytical approach utilizes data reduction through the comparison of interview outcomes with other data. The findings of this study encompass: (1) Streamlining the learning process of Islamic Religious Education to facilitate information retrieval, manipulation, management, and knowledge transfer; (2) Cultivating skills in Information and Communication Technology (ICT) to enhance the smoothness of the learning process; (3) Enhancing teacher professionalism in utilizing YouTube as a medium, particularly in PAI lessons; and (4) Transforming schools into dynamic and creative learning institutions, fostering student motivation and a perpetual curiosity about PAI learning. Effective learning necessitates meticulous planning, including the selection of appropriate media for the learning process. The YouTube application, as a learning support tool, proves highly effective in PAI education in the technology era, both generally and specifically within SMA Ardaniah Serang Banten.Keyword : Learning Media; YouTube Media; Fiqh Learning